A statistical analysis of the factors affecting the economic situation of women within the results of the Iraq Knowledge Network survey - Hani Abdullah Hassan; Ikhlas Abdul Amir Hamid (Iraqi Journal for Administrative Sciences, 2024)
The approach of woman working is not state-specific, but is present in the world as a whole, despite the accompanying this issue in Iraq from the specificities of historical roots and different social and economic van to the problem characteristics it shares with the whole world. The Research trying to study the economic conditions of Iraqi working women in the age group between (15-64) years, which represents the working age and the level of Iraq's provinces and bug level environment (urban, rural) in an attempt to uncover the reasons for the faltering process to empower women economically by identifying the factors influencing women's ability to work, where it was used data scan network know Iraq who carried out in 2011 by the Central Bureau of Statistics and Information Technology, which was adopted in this research as a sample cluster size (29.587) thousand families are females of working age, including the proportion (50.3%) and by (51 828) thousand Female, The data were analyzed by bag statistical programs ready (SPSS VERSION 20) to get to the economic and social variables with the greatest impact on the standard of living of women using the two methods of statistical tools in the field of data analysis multivariate which cluster analysis and factor analysis. The percentage of women working to (13.2%) at the level of Iraq and (11%) in urban areas and (14%) in rural areas with high proportion of women in paid employment in urban areas to (9%) and increase the percentage of women working in their families without pay to (11%) in rural areas, and increase the percentage of unmarried widows of up to (9%) at the level of Iraq and the urban environment and (8%) in rural areas.Also, the province of DhiQar, and at the level of the environment (urban, rural) represents the lowest spending rate for women, while the provinces of Arbil and Sulaymaniyah represent the highest rate of women and spending on the environment (urban, rural). Results showed global that there are six factors moral control variables seventeen placed Find the level of Iraq and at the level of urban environment also that there are five factors significant other at the level of environment countryside, where the variables (labor cases) have had the greatest impact in the formation of first factor on the level of Iraq and the level of the environment (urban, rural).